The effect of tuning the microstructure of TIPS-tetraazapentacene on the performance of solution processed thin film transistors - Paulus, Fabian; Engelhart, Jens U.; Hopkinson, Paul E.; Schimpf, Christian; Leineweber, Andreas; Sirringhaus, Henning; Vaynzof, Yana; Bunz, Uwe H. F. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2016)
We report a comprehensive study of the symmetrical 6,13-bis(triisopropylsilylethynyl)tetraazapentacene (TIPS-TAP) used as an electron transporting material in organic field-effect transistors. We study the optical, electronic, structural and morphological properties of thin films of TIPS-TAP as deposited by spin-coating and zone-casting techniques. Depending on the solution processing conditions and procedures we find a variety of microstructures for TIPS-TAP ranging from highly polycrystalline to well-aligned crystalline films. Field-effect transistors are fabricated in two different architectures to evaluate the charge transport properties of TIPS-TAP in such films, and bias-stress experiments reveal a good electric stability of TIPS-TAP. The extracted electron mobilities vary over several orders of magnitude depending on the resulting morphology of the active layer reaching a maximum of 0.42 cm2 V−1 s−1 for uniaxial aligned crystallites in zone-cast transistors.